Smart-Working and Hot Desking Application Development using Agile and Extreme Programming Method at Xtra Cowork - Nurdin, Daeng Ahmad; Firmansyah, Dodik; Hafifi, Akrom; Darwis, Muhammad (Universitas Trilogi, 2024)
The current condition of working desks often faces challenges such as poor management and inefficiency in space utilization, which complicates the adoption of Smart-Working culture at Xtra Cowork. To address these issues, the writer aims to facilitate the transition for offices adopting Smart-Working culture by designing a hot desking supporting mobile app. Through observation, the research identifies the need for a reliable system to support hot desking practices. To complete this research, the writer uses agile and extreme programming methods. For app designing, the writer uses UML. The main tools used for developing the app are Flutter with Dart language. The developed mobile app successfully fulfills these requirements. The results of the application testing using the black box method has passed 100% of the test cases. It shows that all functions have worked as designed and could be used by the users as intended. Future researchers can build upon this work to address other Smart-Working culture needs.